Digging for the history of man. part 1 3000 B.C. - 600 A.D. (Roland films on art, 1987)
A survey of the archeological explorations in which evidence of the art and architecture of the Babylonians. Supernumeraries, Hittites, Greeks, and Romans was discovered.